Effectivity of Esomeprazole Compared with Lansoprazole in the Treatment of Pediatric with Gastritis - Kollins, Fini; Supriatmo, Supriatmo; Saragih, Rina; Ilhamd, Ilhamd (Open access Macedonian journal of medical sciences, 2021)
BACKGROUND: The administration of proton pump inhibitor (PPI) therapy in pediatric patients has also increased dramatically during the last three decades. Clinical trials comparison of esomeprazole and lansoprazole for pediatric were limited. AIM: This study focused on comparing the effectivity of Esomeprazole with lansoprazole for healing gastritis symptoms in pediatric patients. METHODS: A randomized and single blind (assessors) controlled clinical trial was done at H. Adam Malik hospital at Medan. Patients that complied with study’s criteria and signed informed consent were collected information about the symptoms. Confirmation diagnosis of g astritis by gastroscopy, then randomized into lansoprazole treatment group (15 mg if < 30 kg and 30 mg if > 30 kg) or esomeprazole treatment group (0,4–0,8 mg per Kg body weight). Medication for both groups will be given orally for 14 day s, then evaluated for the initial symptoms. p -value of this study was calculated with the χ2 test. RESULTS: Fifty two patients confirmed gastritis were enrolled in this study; 27 patients received lansoprazole and 25 patients received esomeprazole. There was no difference of effectivity between the two groups for vomiting, hematemesis, and nausea. Lansoprazole treatment for 14 days has a significant difference for abdominal pain recovery from esomeprazole treatment. The lansoprazole groups have 92% free of abdominal pain compared to the esomeprazole group for only 66% free of abdominal pain. CONCLUSION: There was no significant difference between lansoprazole and esomeprazole therapy.